Efficacy of a sports specific balance training programme on the incidence of ankle sprains in basketball - Cumps, E.; Verhagen, E.; Meeusen, R. (Journal of Sports Science & Medicine, 2007)
The purpose of the study was to determine the efficacy of a 22- week prescribed sports specific balance training programme on the incidence of lateral ankle sprains in basketball players. A controlled clinical trial was set up. In total 54 subjects of six teams participated and were assigned to either an intervention (IG) or a control group (CG). The IG performed a prescribed balance training programme on top of their normal training routine, using balance semi-globes. The programme consisted of 4 basketball skills each session and its difficulty was progressively thought-out. The intervention lasted 22 weeks and was performed 3 times a week for 5 to 10 minutes. Efficacy of the intervention on the incidence of lateral ankle sprains was determined by calculating Relative Risks (RR, including their 95% Confidence Intervals or CI) and incidence rates expressed per 1000h. RR (95% CI) showed a significantly lower incidence of lateral ankle sprains in the IG compared to the CG for the total sample (RR= 0.30 [95% CI: 0.11-0.84]) and in men (RR= 0.29 [95% CI: 0.09-0.93]). The difference in RR was not confirmed when examining the incidence rates and their 95%CI's, which overlapped. The risk for new or recurrent ankle sprains was slightly lower in the IG (new: RR= 0.76 [95% CI: 0.17-3.40]; re-injury: RR= 0.21 [95% CI: 0.03-1.44]). Based on these pilot results, the use of balance training is recommended as a routine during basketball activities for the prevention of ankle sprains.